2016
DOI: 10.3389/fnbeh.2016.00112
|View full text |Cite
|
Sign up to set email alerts
|

Non-anemic Iron Deficiency from Birth to Weaning Does Not Impair Growth or Memory in Piglets

Abstract: Early iron deficiency is associated with impaired (cognitive) development, the severity of which depends on the timing and duration of the under-supply of iron. To design effective treatment and prevention strategies for iron deficiency in humans, suited animal models are needed. In an earlier study (Antonides et al., 2015b) we separated 10 pairs of piglets from their mothers within a few days after birth and reared one sibling with artificial iron-deficient (ID) and the other with balanced control milk until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
9
0
2
Order By: Relevance
“…Taken together, the effects of iron deficiency on the infant can be severe, especially if iron deficiency is left untreated and progresses to IDA. The extent of detrimental outcomes in response to iron deficiency are dependent on the timing and severity of deficiency experienced [ 3 , 4 ]. Clinically, the most significant impact of IDA are effects on red blood cells, though this is known to recover quickly with dietary iron repletion.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the effects of iron deficiency on the infant can be severe, especially if iron deficiency is left untreated and progresses to IDA. The extent of detrimental outcomes in response to iron deficiency are dependent on the timing and severity of deficiency experienced [ 3 , 4 ]. Clinically, the most significant impact of IDA are effects on red blood cells, though this is known to recover quickly with dietary iron repletion.…”
Section: Introductionmentioning
confidence: 99%
“…Adejinmi et al, (2004) reported anaemia as a reliable indicator for the severity of haemoparasitic infections. 4.58% of the total blood sample was parasitemic and showed anaemia, while 0.65% were parasitemic but did not show anaemia, this could be due to a low parasitaemia or dehydration (Antonides et al, 2016), 36.60% of the total blood samples were anaemic but aparasitaemic and this could be as a result of other causes of anaemia such as malnutrition (Jennings 1976), stress or other infectious agents asides haemoparasites (Obi and Anosa, 1980), a greater percentage (58.17%) of the blood sample were non-anaemic and aparasitemic. Eperythrozoon suis caused more severe anaemia (20 ± 9.89) compared with Trypanosoma brucei (27 ± 3.03).…”
Section: Discussionmentioning
confidence: 92%
“…Porcine milk is known to have low iron concentrations; as such, it is common agricultural practice to supplement piglets with an iron dextran injection to deliver ;250 mg Fe early in life. As a follow-up study to their artificially reared iron-deficient piglets, Antonides et al (71) assessed iron deficiency in piglets that were maternally reared and then provided iron-replete feed from 4 to 16 wk of life. Sibling pairs were divided into 2 groups, iron deficient (i.e., saline injection on days 3 and 10 of life) or iron sufficient (i.e., iron dextran shot on days 3 and 10 of life), and allowed to ingest maternal milk throughout the preweaning period.…”
Section: Micronutrientsmentioning
confidence: 99%